Sep analysis of estimated channel in decode-and-forward cooperative networks - Do Dinh Thuan (Journal of Technical Education Science, 2014)
When the sizes of end-user equipments are limited, the cooperative relay networks are recommended as promising virtual MIMO systems to improve the performance of wireless communication systems in literature. In this paper, we focus on performance analysis of two- hop relay wireless networks using Decode-and-Forward (DF) scheme. Specifically, we derive the closed-form expression of symbol error probability (SEP). Thanks to utilizing least square- based channel estimation algorithm in calculation of instantaneous channel state information (CSI), we obtain approximate SEP based on the estimated channel states and the decoding state at the relay nodes. The SEP approximation formula is used to assess the power allocation in dual-hop networks. Simulation results for a two-hop system with optimal SEP show significant improvement.